2022
DOI: 10.3389/fped.2022.818043
|View full text |Cite
|
Sign up to set email alerts
|

Human Trafficking ICD-10 Code Utilization in Pediatric Tertiary Care Centers Within the United States

Abstract: BackgroundHuman trafficking is a global public health issue that affects pediatric patients widely. The International Labor Organization estimates children comprise approximately 25% of the identified trafficked persons globally, with domestic estimates including over 2000 children a year. Trafficked children experience a broad range of health consequences leading to interface with healthcare systems during their exploitation. In June 2018, International Classification of Diseases, Tenth Revision, Clinical Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…We found that the population is predominantly young and female, consistent with reports in the US and some other regions [20]. The population was found to be slightly older and racially more White than reported in an earlier study [17], likely because it utilized data from urban pediatric tertiary medical centers. Generally speaking, it was surprising to see so many victims in our database, which includes just persons holding commercial or government-provided insurance, as it runs counter to the view that few victims would have insurance of any kind.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that the population is predominantly young and female, consistent with reports in the US and some other regions [20]. The population was found to be slightly older and racially more White than reported in an earlier study [17], likely because it utilized data from urban pediatric tertiary medical centers. Generally speaking, it was surprising to see so many victims in our database, which includes just persons holding commercial or government-provided insurance, as it runs counter to the view that few victims would have insurance of any kind.…”
Section: Discussionsupporting
confidence: 89%
“…Because administrative claims data is used for billing, providers might be using more conventional codes where they are more certain of receiving payment. Additionally, patients and providers might be concerned about whether the trafficker has access to the medical records of the patient or not, which might make the providers hesitant about using the new ICD-10 codes [17]. But we hypothesize that the lack of awareness and absence of institutional policies are the primary causes of underreporting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature review with Pubmed, Scopus, Web of Science, and Google Scholar shows that there have been few studies based on the new ICD-10 codes. The two largest previous studies utilizing these codes relied on 49 pediatric tertiary centers ( 16 ) and 48 healthcare organizations ( 17 ). Another study ( 18 ) interviewed providers and examined their awareness of human trafficking but did not quantify the characteristics of the trafficked population.…”
Section: Introductionmentioning
confidence: 99%